Strategic human resource management technology effect and implication for distance training and learning - khalil alsaadat (Institute of Advanced Engineering and Science, 2019)
Strategic human resource management involves a future-oriented process of developing and implementing HR programs that address and solve business problems and directly contribute to major long-term business objectives. HR management has changed dramatically in recent decades. It was once largely an administrative function focused on day-to-day responsibilities such as employee recruiting and selection and managing employee benefits. Changing labor market conditions and new business thinking call for HR business strategies that include recruiting and retaining the right people, as well as providing ethical and cultural leadership[1].This paper discusses the following issues : The importance of human resource activity , The importance of strategic human resource planning, The changing role of human resource management and nature of work and non government organizations , Technology effect on human resource management and implications for distance training and learning .A field study was conducted to know the attitude of one hundred and five Saudi employees towards the effect of distance learning and training on human resource management and development